New data regarding the bumblebee fauna (Hymenoptera: Apidae) of the northern part of Murmansk Region - Grigory Sergeevich Potapov; Anastasia Pervukhina; Galina Bovykina; Yulia Kolosova; Alexander Kondakov (Fauna Norvegica)
The focus of this study is to present new data regarding the bumblebee fauna of the northern part of Murmansk Region (Northern European Russia). A total 15 species of bumblebees were found here that cover almost all species that may be found in the studied area. Bombus sporadicus and B. bohemicus are the first records in the northern part of Murmansk Region, but these species are well known from Northern Fennoscandia. No new haplotypes were found for B. alpinus and B. monticola in the Kola Peninsula. They belong to the lineages which are common in Scandinavia and Finland.